The Role of Teachers in Improving Student Learning Outcomes During the COVID-19 Pandemic - Ardi Wijayanto; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2022)
The role of the teacher in any circumstances and conditions is still prioritized in improving student learning outcomes. So that learning can still run effectively so that the process can run as it should. During the COVID-19 pandemic at SMAN 2 Kinali, there was a decrease in student learning outcomes. Research purposes, in this case, are to find out how the role of teachers in improving learning outcomes during the COVID-19 pandemic. The method used is a literature review from various journals and book sources that are on the theme. The role of teachers in improving student learning outcomes during the COVID-19 pandemic at SMAN 2 Kinali can be done by increasing aspects of the role and function of teachers in learning, factors that affect learning, learning outcomes, and learning during the COVID-19 pandemic.